THE INFLEUNCE OF TRANSCRANIAL MAGNETIC STIMULATION (TMS) ON EPILEPTIFORM ACTIVITY IN RATS WITH PHARMACOLOGICAL KINDLING - Kobolev, E.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
TMS of low frequency (1/s, during 10 s) and relatively high induction of magnetic field at the peak of its development (1,0-1,5 Tl ) prevented the precipitation of kindled generalized clonic- tonic fits and reduced the duration of epileptic discharge (25,7+2,9 s while in sham-TMS rats it was 44,5+5,2 s (P<0,05). Investigation of the total power of EEG in the course of epileptiform activity (EpA) development revealed the decrease of total power of EEG in all investigated structures in TMS- rats (by 18% in comparison with the kindled sham- TMS rats) during the initial part of EpA development (first 15 s). At the end of EpA (last 15 s) such differences were kept in hippocampus, occipital, and frontal cortical zones. Analysis of the different bandwidths contribution to the total power of EEG showed that at the moment of EpA cessation most contributive was the reduction of tetha, beta and gamma rhythms while delta rhythm was developed in counterpart to these changes. Hence, the correspondance of gauned data to that one which were received under conditions of electrical kindling are under discussion.